Scotogenic Froggatt-Nielsen and the versatility of soft symmetry breaking - Ernest Ma (Physics Letters B)
Preserving the unique role of the one Higgs doublet of the standard model, it is proposed that quark and lepton mass patterns, often ascribed to the Froggatt-Nielsen mechanism using nonrenormalizable higher-dimensional terms, may be enforced in a renormalizable theory of just one Higgs doublet by the scotogenic mechanism with soft symmetry breaking in the dark sector. A revised version of the original A4 model of charged leptons and neutrinos is discussed.